The influence of playing surface on the movement characteristics of small-sided games in highly trained pre-pubertal soccer players - Fenner, J.; Iga, J.; Drust, B.; Barrett, S.; Unnithan, V. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Small-sided games (SSG`s) are commonly used training modality and recently adapted for use as a talent identification model (Unnithan et al. 2012). In youth soccer, training schedules are organised on a large scale and, therefore, require significant artificial turf usage, as natural turf pitches are sensitive to frequent use and cold climates. Movement characteristics and physiological responses on natural and artificial turf are noted to be similar in full-sized adult games; however no study has investigated these effects during SSG in pre-pubertal players. The aim of this study was to assess movement characteristics and physiological responses during multiple SSG on artificial turf compared to natural turf. Methods: Eight pre-pubertal soccer players (age: 10.4 ± 0.2 yrs) from a professional youth soccer academy were recruited. Three, 4 vs. 4 SSG games were played on both artificial and natural turf. Each game was 5 min in duration, interspersed with 3 min rest. The same combination of players was used for each game, on each playing surface. Pitch size was identical for both surfaces (18.3 m x 23 m). Movement characteristics were captured using micromechanical devices (MEMS). Heart rate (HR) was recorded using short-range radio telemetry. A two factor, mixed design analysis of variance (ANOVA) was used to analyse the data. Results: Mean HR was not significantly different between the surfaces (Game 1: Natural 152 ± 15 bpm vs Artificial 158 ± 33 bpm, Game 2: Natural 151 ± 16 bpm vs Artificial 156 ± 20 bpm, Game 3: Natural 157 ± 16 bpm vs Artificial 156 ± 25 bpm). Player load was not significantly different between the surfaces (Game 1: Natural 52 ± 3 Au vs Artificial 58 ± 6 Au, Game 2: Natural 52 ± 5 Au vs Artificial 55 ± 6 Au, Game 3: Natural 53 ± 6 Au vs Artificial 53 ± 4 Au). Discussion: There was no significant difference in either internal physiological load or movement characteristics in SSG when played on artificial or natural turf in this age group. This indicates that artificial turf does replicate natural turf, with regard to the consistency of the movement characteristics and the internal physiological load when playing multiple SSG, but the findings are delimited to this particular age group. Consequently, the use of artificial pitches can be advocated as an appropriate surface for achieving training or talent identification-related objectives from SSG in pre-pubertal players.